GRANULOMATOUS DISEASE-INDUCED SEVERE HYPERCALCEMIA - Muhammad, Nur Farrah Anima; Jalal, Fadzliana Hanum; Kamil, Mohd Khairul Mohd (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Hypercalcemia is commonly seen in granulomatous disease especially in sarcoidosis in around 40-50% cases; however, lower rates of association have been reported in tuberculosis. The etiology is due to the production of extrarenal 1-alpha-hydroxylase enzymes by activated macrophages seen in the granulomas. This will then lead to inappropriately elevated 1,25-dihydroxyvitamin D causing dysregulation of calcium metabolism. CASE A patient with a known case of disseminated tuberculosis (TB) was admitted to critical care with an initial impression of cerebral toxoplasmosis. Throughout his admission, blood parameters were closely monitored which revealed moderate to severe hypercalcemia ranging from 2.8–4.0 mmol/L with clinical features of nephrogenic diabetes insipidus (polyuria of 5440 ml urine output per day, hypernatremia ranging 147–157 mmol/L (135–145 mmol/L) and low urine osmolality 143 mOsm/kg). However, despite treatment with hydration, severe hypercalcemia resulted in the atypical presence of J-wave or Osborn wave on electrocardiogram (ECG). Hypothermia has been ruled out as his body temperature ranges from 36.7–37 °C. There is no interruption in his TB medications and iatrogenic causes have also been excluded. Intact parathyroid hormone (iPTH) yielded a low result of 1.61 pmol/L (1.95–8.49 pmol/L). Overall features point to non-iPTH dependent hypercalcemia. Corticosteroid therapy with IV hydrocortisone 50 mg TDS together with subcutaneous calcitonin 100 IU TDS were initiated. Bisphosphonate therapy consisting of one dose of intravenous zoledronic acid 4 mg was added to the therapeutic regimen the next day. After 3 days of treatment, hypercalcemia resolved with corrected calcium ranging from 1.7–2.3 mmol/L. The patient unfortunately succumbed to overwhelming sepsis with multiorgan involvement. CONCLUSION Granuloma-induced hypercalcemia remains a diagnostic challenge in persons with TB due to its uncommon occurrence. However, there must be a high index of suspicion to facilitate early intervention with calcium-lowering drugs to avoid morbidity and mortality in such patients.